Indigenous youth and multilingualism: Language identity, ideology, and practice in dynamic cultural worlds. - Kvietok Dueñas, Frances (Revista Peruana de Investigación Educativa, 2016)
Wyman, L. T., McCarty, T. L. y Nicholas S. E. (Eds.) (2014). Indigenous youth and multilingualism: Language identity, ideology, and practice in dynamic cultural worlds. New York: Routledge